Leukoaraiosis and intracerebral hemorrhage after thrombolysis in acute stroke. - Palumbo, V; Boulanger, J; Hill, MD; Inzitari, D; Buchan, A (2007)
OBJECTIVES: To evaluate whether the presence of leukoaraiosis or multiple lacunes is associated with symptomatic intracerebral hemorrhage (ICH) and 90-day outcome after thrombolytic treatment with tissue plasminogen activator (tPA). METHODS: Data were from a Canadian national registry of thrombolyzed patients with ischemic stroke. A total of 820 scans were assessed, blind to clinical features, for the presence of severe vs no/moderate leukoaraiosis, and of multiple (>2) vs no/single lacunar infarcts. Logistic regression was used to determine if an independent interaction existed between the presence and degree of leukoaraiosis/lacunes and risk of symptomatic ICH, and to evaluate the predictive role of leukoaraiosis and lacunes in relation to 90-day outcome. RESULTS: An overall symptomatic ICH rate of 3.5% was observed. The rate of symptomatic ICH increased up to 10% in patients with severe leukoaraiosis and multiple lacunes. A significant association was observed between ICH risk and either severe leukoaraiosis (RR = 2.7 [95% CI 1.1 to 6.5]) or multiple lacunes (RR = 3.4 [95% CI 1.5 to 7.6]). Patients with multiple lacunes, but not leukoaraiosis, had higher mortality at 90 days compared to those with one or no lacunes (OR = 2.9, 95% CI 1.3 to 6.2, p = 0.008). No difference was observed in the good outcome rate among patients with and without leukoaraiosis or lacunes or both. CONCLUSION: The presence of small vessel disease on CT scan does not affect overall clinical outcome at 3 months in routine community use of tPA for ischemic stroke. A significant increase in the risk of symptomatic ICH is observed.